Plan de desarrollo y ordenamiento territorial (PDOT) de la parroquia El Cisne, perteneciente al cantón Loja. - Cuenca Montaño, Fernando Michael (2012)
The Plans of Development and Territorial Parochial Classification are a normative one, with law force that guarantees their sustainable; in this context the present versed investigation as: Plan of Development and Territorial Classification (PDOT) of the parish The Cisne belonging to the cities Loja, to guide the present investigative work I take into account the general objective: Plan of Development and Territorial Classification (PDOT) of the parish The Cisne belonging to the cities Loja, based on this objective it has developed it to him in three parts, a diagnosis for each system: ecological; economic; of human establishments; of mobility and connectivity; cultural partner; and, of management of the territory. The second part, picks up the recommendations and arisen proposals of the work of quick rural approach; later on he/she thinks about the vision that has the so much population of the wanted society, as of the territorial classification of the Parish. Finally, the action lines settle down with the respective programs and projects that will contribute to the development and classification of the parish. The obtained results allow us to arrive to the proposal of a wanted model of the territory, taking in consideration the current diagnosis of the parish; for which intends to conform to an urban structure with an appropriate distribution of activities in the space, so that among them good and functional relationships settle down; at the same time that the balanced development of the populated center is propitiated and it is optimized to the maximum the infrastructure and the equipment urban and rural present and future. In this premise the Parochial Meeting should transform into an organism propiciador of the development, and to impel and to coordinate defined projects as high-priority for the population.